An agroecological vision of perennial agriculture. Issue 10 (26th November 2021) - Reynolds, Jules; Bell, Michael M; Grace, Jacob; Gratton, Claudio; Jackson, Randall D.; Keeley, Keefe O.; Mayerfeld, Diane
ABSTRACT: Not all agriculture based on perennial plants is ecologically sound or socially just. But an agroecological concept of perennial agriculture must be. We suggest three key elements of an agroecological vision for perennial agriculture. First, perennial agriculture must be managed with regard for the future as much as the present. Second, perennial agriculture must be situated in an ecological and social context, meeting the material, social, and ecological needs of the individuals and communities that engage in producing agricultural goods – making it what we term an "agroecological endeavor." Third, perennial agriculture must include a diversity of plants, including – but not limited to – perennial plants. Thus, we propose envisioning perennial agriculture as the perennial management of an agroecological endeavor that includes perennial plants .